Determinants of postharvest losses along the baobab value chain in Malawi - Cossam, Foster Geoffrey; Dzanja, Joseph Kuyamba; Kamwana, Bonnet; Olumeh, Dennis Etemesi; Mithöfer, Dagmar (Frontiers in Sustainable Food Systems, 2023)
Wild fruits like Baobab are gaining status as a valuable food resource worldwide. As with other crops, the reduction of postharvest losses is critical to enhancing sustainable utilisation of wild food resources. However, little information is documented on the magnitude and determinants of postharvest losses (PHLs) among Non-Timber Forest Products (NTFPs), and baobab in particular. This study used cross-sectional data collected from six districts to analyse PHLs along the baobab value chain in Malawi. A multistage sampling technique was used to sample 405 collectors, 96 traders, and 316 processors. Two-limit Tobit models were used to ascertain correlates of PHLs at each value chain level. The study quantified the value of PHLs and assessed the effect of socioeconomic factors on PHLs among baobab actors. We found that actors in the baobab value chain lose 7.78% of the total value of products held through PHLs. The results also showed that different sets of socioeconomic factors variably influenced PHLs among different value chain actors in the baobab value chain. For instance, gender was found to only correlate with PHLs among collectors. While marital status was positively correlated with PHLs among collectors, and had a negative relationship among processors. PHLs at traders’ level are influenced by the number of people employed by an actor, the ability of customers to specify product attributes, and a proportional reduction in sales volume due to COVID-19. The study recommends the provision of training in PHLs management, and the formulating and enforcing of Baobab product handling standards.